Changes in phytohormone content and associated gene expression throughout the stages of pear (Pyrus pyrifolia Nakai) dormancy. (30th September 2019) - Ito, Akiko; Tuan, Pham Anh; Saito, Takanori; Bai, Songling; Kita, Masayuki; Moriguchi, Takaya
Abstract: To elucidate the role of phytohormones during bud dormancy progression in the Japanese pear (Pyrus pyrifolia Nakai), we investigated changes in phytohormone levels of indole acetic acid (IAA), gibberellic acid (GA), abscisic acid (ABA) and trans -zeatin (tZ). Using ultra-performance liquid chromatography/mass spectrometry/mass spectrometry, we monitored phytohormone levels in the buds of field-grown and potted trees that were artificially heated to modify the timing of dormancy and flowering (spring flush) progression. We also analyzed the expression of GA- and ABA-metabolic genes during dormancy. Indole acetic acid and tZ levels were low during dormancy and increased toward the flowering stage. Gibberellic acid levels were maintained at relatively high concentrations during the dormancy induction stage, then decreased before slightly increasing prior to flowering. The low GA concentration in potted trees compared with field-grown trees indicated that GA functions in regulating tree vigor. Abscisic acid levels increased from the dormancy induction stage, peaked near endodormancy release and steadily decreased before increasing again before the flowering stage. The ABA peak levels did not always coincide with endodormancy release, but peak height correlated with flowering uniformity, suggesting that a decline in ABA concentration was not necessary for resumption of growth but the abundance of ABA might be associated with dormancy depth. From monitoring the expression of genes related to GA and ABA metabolism, we inferred that phytohormone metabolism changed significantly during dormancy, even though the levels of bioactive molecules were consistently low. Phytohormones regulate dormancy progression not only upon the reception of internal signals but also upon sensing ambient conditions.